Different MicroRNA Expression Levels in Gastric Cancer Depending on Helicobacter pylori Infection - Chang, Hyun (Gut Liver, 2015)
BACKGROUND/AIMS: This study was conducted to identify microRNAs (miRNAs) that are differentially expressed in Helicobacter pylori-infected patients with an intestinal type of gastric cancer using miRNA microarray and to confirm the candidate miRNA expression levels. METHODS: Total RNA was extracted from the cancerous and noncancerous regions of formalin-fixed, paraffin-embedded tissues of H. pylori-positive (n=8) or H. pylori-negative (n=8) patients with an intestinal type of gastric cancer. RNA expression was analyzed using a 3,523 miRNA profiling microarray based on the Sanger miRBase. Validation analysis was performed using TaqMan miRNA assays. RESULTS: A total of 219 miRNAs in the aberrant miRNA profiles across the miRNA microarray showed at least a 2-fold change differential expression in H. pylori-positive and H. pylori-negative cancer tissues. After candidate miRNAs were selected using online miRNA databases, TaqMan miRNA assays confirmed that three miRNAs (miR-99b-3p, miR-564, and miR-638) were significantly increased in three H. pylori-positive cancer tissues compared to the H. pylori-negative cancer tissues. Additionally, four miRNAs (miR-204-5p, miR-338-5p, miR-375, and miR-548c-3p) were significantly increased in H. pylori-negative cancer tissues compared to H. pylori-positive cancer tissues. CONCLUSIONS: miRNA expression in the intestinal type of H. pylori infection-dependent gastric cancer suggests that different gastric cancer pathogenesis mechanisms could exist between H. pylori-positive and H. pylori-negative gastric cancer. Additional functional studies are required.